Pelatihan Clinical Pastoral Education (CPE) bagi Guru-guru PAK dan Pengurus Gereja Di Wilayah Kabupaten Barito Timur - Wainarisi, Yane Octavia Rismawati; Wilson, Wilson; Bate’e, Yamowa’a; Lepina, Lepina (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The Covid-19 pandemic has attacked every aspect of human life in the last two years. Currently, people are trying to rebuild their lives after the pandemic. But so many people live under various emotional and spiritual pressures. These people are people who need pastoral help. However, the large number of needs is inversely proportional to the number of Pastoral practitioners. For this reason, Christian Community Guidance together with the local church in collaboration with the Palangka Raya IAKN Postgraduate Program conducted Clinical Pastoral Education (CPE) training. The method used in this PKM is the ABCD method because of the large potential of prospective CPE Practitioners in East Barito who can assist in pastoral activities. Training activities that should be carried out by 400 JP are formulated in 4 JP with 2 JP Materials and 2 JP Simulations. From this activity, the management of the GKE Tamiang Layang Resort and the PAK teachers of East Barito are ready to become ready-to-use CPE practitioners in Pastoral services in East Barito district